Indicadores de aptidão física, funcional e de fragilidade: comparação entre idosos com demência diabéticos e não diabéticos - Pedro Tiago Lopes da Costa (2020)
The ageing of the population is the main risk factor for the development of chronic diseases and it is expected that in the coming years the prevalence of elderly people with dementia and diabetes will increase. Both conditions emphasize functional problems and fragility with the potential to impact the quality of life of individuals and the loss of independence. Therefore, this study aims to analyse differences in functional fitness among individuals with dementia diabetics (IwDD) and individuals with dementia without diabetics (IwDwD). The sample of this cross-sectional study consisted of 66 individuals with dementia (78.20 ± 6.50). The individuals were divided into 2 groups: a group of IwDD and another group of IwDwD. The instruments used for the assessment of the indicators of functionality and fragility, were the 2 'Min Step, the Time Up and Go (TUG), the Handgrip and the Short Physical Performance Battery (SPPB) test battery. The results of our study indicated that IwDD had a better cardiorespiratory fitness (p = <0.02), a lower risk of falls (p = <0.024) and better functionality of the lower limbs (p = <0.024) in comparison with the IwDwD. However, no statistically significant differences were found for handgrip outcomes (p = <0.163), between both groups. Our results showed that the elderly in the IwDwD group showed a higher level of functional decline and frailty. These results were promising and came to emphasize the importance of continuing to study this topic with more robust designs and samples.